The role of travel in measles outbreaks in Australia – An enhanced surveillance study. Issue 37 (17th August 2016) - MacIntyre, C.R.; Karki, S.; Sheikh, M.; Zwar, N.; Heywood, A.E.
Highlights: Importation of measles is a continuing threat to disease control in Australia. The most frequent age group notified with measles were older children and teenagers. Over half of all measles cases occurred in Migrants and VFR travellers. Cases of measles occurred in children of vaccine objectors. Young adults and migrants should be a high priority for preventive strategies. Abstract: Many developed countries, like Australia, maintain a high population level immunity against measles, however, there remains a risk of acquisition of measles in non-immune travellers and subsequent importation into Australia leading to localised outbreaks. In this study, we estimate the incidence of measles and describe characteristics including immunisation and pre-travel health seeking behaviour of notified cases of measles in New South Wales and Victoria, Australia between February 2013 and January 2014. Cases were followed up by telephone interview using a questionnaire to collect information of demographic and travel characteristics. In NSW, the incidence was highest in age group 0–9 years (20/million population) whereas in Victoria the highest incidence was observed in 10–19 (23/million population) years group. Out of 44 cases interviewed, 25 (56.8%) had history of travel outside of Australia during or immediately prior to the onset of measles. Holiday (60%) was the main reason for travel with 44% (11/25) reporting visiting friends and relatives (VFR) during the trip. The major reason described for not seeking prior medical advice before travel were "no perceived risk of diseases" (41%) and "previous overseas travel without any problem" (41%). Of the 25 measles cases with recent overseas travel during the incubation period, one reported a measles vaccine prior to their recent trip. Four cases were children of parents who refused vaccination. Twenty out of 25 (80.0%) had attended mass gathering events. Young adults and VFR travellers should be a high priority for preventive strategies in order to maintain measles elimination status.